Numerical Analysis of Rarefied Gas Flow through a Periodic System of Channels - Voronich, I. V.; Titarev, V. A.; Kudriashov, A. V. (Fluid dynamics, 2025)
Rarefied gas flows through a planar periodic system of rectangular channels (membrane) are analyzed in a wide range of Knudsen numbers. The problem is studied based on the numerical solution of the kinetic equation with the Shakhov S -model collision integral and the Navier–Stokes equations of the compressible medium. The main attention is paid to the calculation of the mass flow rate as a function of the permeability, the relative channel length, and the rarefaction parameter.